2020
DOI: 10.1038/s41598-020-65294-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of posterior semicircular canal function in idiopathic sudden sensorineural hearing loss

Abstract: Predicting hearing outcomes in idiopathic sudden sensorineural hearing loss (ISSNHL) is still challenging. We hypothesized that assessment of the semicircular canal (SCC) function via the video head impulse test (vHIT) might provide prognostic information. The medical records of patients diagnosed with ISSNHL from January 2015 to December 2018 were retrospectively reviewed. The prognostic values of the vHIT and other previously known factors in predicting hearing recovery were analyzed using a logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 31 publications
5
45
0
Order By: Relevance
“…Furthermore, a significant difference in the abnormal rate of the PSC was found between SSNHL patients with or without vertigo in our study. Studies have also suggested that vestibular dysfunction is likely to extend from organs close to the cochlea to organs farther from the cochlea ( 15 , 27 ). In our opinion, the reason for the inconsistent results may be the different audiogram configurations used for SSNHL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a significant difference in the abnormal rate of the PSC was found between SSNHL patients with or without vertigo in our study. Studies have also suggested that vestibular dysfunction is likely to extend from organs close to the cochlea to organs farther from the cochlea ( 15 , 27 ). In our opinion, the reason for the inconsistent results may be the different audiogram configurations used for SSNHL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al demonstrated that the functions of vestibular organs, particularly the utricle and HSC, are associated with disease severity and hearing outcome in patients with SSNHL ( 14 ). Byun et al studied the function of each semicircular canal and saccule using vHIT, cVEMP, and caloric tests, and found that abnormal vHIT gain in the posterior semicircular canal (PSC) appears to be a specific prognostic factor for incomplete hearing recovery in SSNHL ( 15 ). Various inconsistent results were presented regarding involved vestibular dysfunction in patients with SSNHL depending on the presence of vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…The presumed causes of SSNHL include autoimmune inner ear diseases, viral infections, vascular disorders, ototoxic medication, genetic disorders, trauma, and acoustic tumors, but in most cases, the etiology is uncertain [14,22]. As opposed to noise-induced hearing loss, where one can study cochlear synaptopathy in noise-exposed animal models, it is impossible to design animal models to study the pathophysiology of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…For ISSNHL patients with acute vertigo, some novel characteristics of vestibular lesions have been detected by vHIT recently ( 3 , 10 ). Most of these patients exhibited posterior SCC dysfunction ( 3 , 11 ), which could serve as a specific prognostic tool for predicting poor hearing recovery in patients with ISSNHL ( 12 ). VN, another typical variant of acute vestibular syndrome, shows mainly vestibular impairment in the horizontal and anterior SCC (as in superior VN).…”
Section: Introductionmentioning
confidence: 99%